2011
DOI: 10.2224/sbp.2011.39.10.1403
|View full text |Cite
|
Sign up to set email alerts
|

Regional Differences in Customer Satisfaction in China

Abstract: Regional differences in customer satisfaction were examined, with a focus on the relationship between economic development and customer satisfaction. The moderating roles of regional economic development on the associations between customer satisfaction and its antecedents were also examined. Participants were 11,042 consumers in 8 durable goods categories across 21 cities in China. Results based on hierarchical linear models suggest that customer satisfaction with products is negatively related to regional ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
0
4
0
3
Order By: Relevance
“…Además de ello, las diferencias contextuales juegan un papel importante en el comportamiento de las relaciones funcionales (Ledden, Kalafatis, & Mathioudakis, 2011), por lo que también puede influir en el desfase encontrado el haber realizado los trabajos en países geográfica y culturalmente muy distantes (Brady et al, 2005;Huang et al, 2011;Nuviala et al, 2012a). Así mismo, el no encontrar relación directa no excluye que en el caso de incluir algún mediador pudiese aparecer relación indirecta (Forgas et al, 2012).…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Además de ello, las diferencias contextuales juegan un papel importante en el comportamiento de las relaciones funcionales (Ledden, Kalafatis, & Mathioudakis, 2011), por lo que también puede influir en el desfase encontrado el haber realizado los trabajos en países geográfica y culturalmente muy distantes (Brady et al, 2005;Huang et al, 2011;Nuviala et al, 2012a). Así mismo, el no encontrar relación directa no excluye que en el caso de incluir algún mediador pudiese aparecer relación indirecta (Forgas et al, 2012).…”
Section: Discussionunclassified
“…Aunque Martínez (2009) afirma que ha alcanzado un nivel similar al de otros sectores económicos, la gestión de la calidad en la industria deportiva aún está en etapa formativa (SzabÓ, 2010). Más investigaciones al respecto son necesarias (Martin & O'Neill, 2010), máxime si consideramos que los aspectos que determinan la satisfacción varían de una región a otra (Brady, Knight, Cronin, Hult, & Keillor, 2005;Huang, Wang, & Chen, 2011).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Except these indices, there have been many other national customer satisfaction indices such as the German Customer Barometer (Meyer and Dornach, 1996), the Danish Customer Satisfaction Index (Martensen et al, 2000), the Norwegian Customer Satisfaction Barometer (Andreassen and Lindestad, 1998), the Pan-European Customer Satisfaction Index (Eklof and Westlund, 2002), the Jordanian Customer Satisfaction Index (Al-Nasser et al, 2011), the Mexican User Satisfaction Index (Calleros et al, 2012), the Chinese Customer Satisfaction Index (Huang et al,2011), the Turkish Customer Satisfaction Index (Turkyilmaz and Ozkan,2007).…”
Section: National Customer Satisfaction Indices: a Model Example For mentioning
confidence: 99%
“…Huang et al (2011) investigated how satisfaction with products differed between developed and non-developed regions of China. It was found that regions with higher levels of economic development were associated with the more critical rating of products.…”
mentioning
confidence: 99%